MANAGEMENT SYSTEM OF SAPTA PESONA TOURISM TUMPAK SEWU WATERFALL ON THE INCOME OF THE LOCAL COMMUNITY IN THE PERSPECTIVE OF SHARIA ECONOMICS - Musthafa Syukur; Karomatun Annisak (Universitas Muhammadiyah Surabaya, 2026)
This research is motivated by the importance of tourism management based on Sapta Pesona in improving the quality of destinations while encouraging the economic growth of local communities. Tumpak Sewu Waterfall, as a leading destination, has great potential that needs to be managed systematically and sustainably. This research aims to analyze the tourism management system based on Sapta Pesona and its contribution to increasing the income of local communities. The method used is a qualitative approach with a case study design, through interview techniques, documentation, and findings in the field. The results of the study show that the implementation of Sapta Pesona is effective in increasing tourist satisfaction and experience, which has an impact on increasing the number of visits. Community involvement through MSME activities such as homestays, guide services, and culinary businesses is the main factor in increasing income. In addition, Sharia economic principles such as honesty and justice also strengthen the sustainability of the local economy. The implications of this study affirm the importance of integration between Sapta Pesona, community-based tourism, and sharia economic value in creating sustainable and inclusive tourism.